Genome-wide analysis of Hsp40 and Hsp70 gene family in four cotton species provides insights into their involvement in response to Verticillium dahliae and abiotic stress - Zhou, Xin; Su, Ling; Tang, Rui; Dong, Yuxuan; Wang, Fei; Li, Rong; Xie, Quanliang; Zhang, Xianliang; Xiao, Guanghui; Li, Hongbin (Frontiers in Genetics, 2023)
Cotton is an important economic crop to provide natural fibers as raw materials to textile industry, and is significantly affected by biotic and abiotic stress during the whole growth stage, in which Verticillium wilt (VW) caused by Verticillium dahliae is one of the most destructive disease to lead to a significant yield reduction. Heat shock proteins (Hsps) are important molecular chaperones, and play crucial roles in plant growth, development, resistance to biotic and abiotic stress. Hsp40 and Hsp70 are two key Hsps in cell chaperone network, however, the function and regulatory mechanism of Hsp40 and Hsp70 members in VW resistance and abiotic stress in cotton are largely unknown. Herein, a systematic and comprehensive analysis of Hsp40s and Hsp70s in four cotton species of Gossypium arboretum, G. raimondii, G. hirsutum, and G. barbadense were performed. A total of 291 Hsp40s and 186 Hsp70s identified in four Gossypium species. Sequence analysis revealed that all Hsp40 proteins contained J domain that provides the binding sites to Hsp70, and the Hsp70s included the highly conserved functional domain with ATPase activity in the N-terminus. Protein-protein interaction prediction analysis displayed that GhHsp40-55 might interact with GhHsp70-2 and GhHsp70-13, suggesting their potential function as a protein complex. Further expression analysis showed that eight GhHsp40s (Hsp40-2,4,8,11,20,23,53,55) and seven GhHsp70s (Hsp70-2,3,6,8,13,19,22) were up-regulated after V. dahliae infection. In addition, five GhHsp40s (Hsp40-2,8,11,53,55) and four GhHsp70s (Hsp70-3,6,8,13) were up-regulated after salt treatment, six GhHsp40s (Hsp40-4,11,20,23) and three GhHsp70s (Hsp70-2,8,19) were up-regulated after drought treatment, four GhHsp40s (Hsp40-2,11,20,23) and four GhHsp70s (Hsp70-3,6,19,22) were up-regulated after temperature treatment, suggesting these Hsps possible have important function in the process of abiotic stress response. Protein-protein interaction prediction analysis indicated that Gaf2, HscB, Ar192, Tim44 and Mge1 have the possible interaction with Hsp40-Hsp70 to form a triplet protein complex to involve in biotic and abiotic response process. Our results lay a foundation for understanding the function of Hsp40 and Hsp70 in the resistance against V. dahliae and abiotic stress, and elucidating the regulatory mechanism of the protein complex, evolution and molecular mechanism under stress.